2011
DOI: 10.1021/jp2036444
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer in Single-Stranded DNA-Templated Stacks of Naphthalene Chromophores

Abstract: We have investigated energy transfer in a novel self-assembled DNA hybrid structure composed of diaminopurine-equipped naphthalene derivatives that are hydrogen-bonded along a single-stranded oligothymine template. By performing time-resolved measurements of the naphthalene donor luminescence decay in the absence and presence of a cyanine Cy3.5 acceptor bonded covalently to the 5′ end of the oligothymine, we have examined the role of temperature and DNA template length on energy transfer from donors to the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 73 publications
1
13
0
2
Order By: Relevance
“…Polymeric and dendritic materials appear particularly promising in this context, due to the covalent joining of large numbers of light absorbing molecules. [24][25][26][27][28][29][30][31][32][33][34][35][36] Alternatively, DNA has been used as a supramolecular scaffold [37][38][39][40][41][42][43][44][45][46][47][48][49] for the construction and the study of light-harvesting antenna systems. We have recently reported on the assembly of water soluble linear [50,51] and two-dimensional [52] supramolecular polymers [53][54][55][56][57] from short amphiphilic pyrene oligomers (oligopyrenotides).…”
mentioning
confidence: 99%
“…Polymeric and dendritic materials appear particularly promising in this context, due to the covalent joining of large numbers of light absorbing molecules. [24][25][26][27][28][29][30][31][32][33][34][35][36] Alternatively, DNA has been used as a supramolecular scaffold [37][38][39][40][41][42][43][44][45][46][47][48][49] for the construction and the study of light-harvesting antenna systems. We have recently reported on the assembly of water soluble linear [50,51] and two-dimensional [52] supramolecular polymers [53][54][55][56][57] from short amphiphilic pyrene oligomers (oligopyrenotides).…”
mentioning
confidence: 99%
“…By varying the size of the template from 10 to 40 thymine units, the researchers observed an optimum in the acceptor emission for a stack of 30 donor chromophores (Figure , bottom). The combination between time‐resolved spectroscopy and molecular modelling simulations showed that, for longer templates, efficient energy transfer occurs in excess of that expected with simple Förster Resonance Energy Transfer calculations …”
Section: Towards Functional Self‐assembliesmentioning
confidence: 99%
“…Bottom: fluorescence spectra (excitation at 400 nm) for DNA templates of different lengths (from 10 to 40 thymine units). Adapted with permissions from references and . Copyrights 2011 American Chemical Society and 2011 The Royal Society of Chemistry.…”
Section: Towards Functional Self‐assembliesmentioning
confidence: 99%
“…In natürlich vorkommenden lichtsammelnden Komplexen (LHCs) werden Photonen durch geometrisch definierte Anordnungen proteingebundener Farbstoffmoleküle absorbiert. [24][25][26][27][28][29][30][31][32][33][34][35][36] Eine andere Mçglichkeit besteht in der Verwendung der DNA als supramolekulares Gerüst [37][38][39][40][41][42][43][44][45][46][47][48][49] für die Konstruktion und Untersuchung lichtsammelnder Antennensysteme. Das Design und die Entwicklung künstlicher lichtsammelnder Systeme sind eine akademische und industrielle Herausforderung mit weitreichenden çkonomischen und çkologischen Auswirkungen.…”
unclassified
“…Polymere und dendritische Materialien scheinen zu diesem Zweck besonders vielversprechend, da in diesen Anordnungen eine Vielzahl von absorbierenden und leitenden Molekülen kovalent miteinander verbunden ist. [24][25][26][27][28][29][30][31][32][33][34][35][36] Eine andere Mçglichkeit besteht in der Verwendung der DNA als supramolekulares Gerüst [37][38][39][40][41][42][43][44][45][46][47][48][49] für die Konstruktion und Untersuchung lichtsammelnder Antennensysteme. Wir berichteten kürzlich über die Herstellung wasserlçslicher linearer [50,51] und zweidimensionaler [52] supramolekularer Polymere [53][54][55][56][57] aus kurzen, amphiphilen Pyrenoligomeren (Oligopyrenotiden).…”
unclassified